Coffee Consumption Transformation in Pontianak through Baudrillard’s Consumer Society Perspective - Desca Thea Purnama; Afwa Anisa; Septiana; Naswa Anindya; Ya'M Adriyan Wijaya (UIN Siber Syekh Nurjati Cirebon, 2026)
This study examines the transformation of coffee consumption practices in Pontianak City through Jean Baudrillard’s consumer society perspective. Using a qualitative approach, data were collected through interviews, observations, and documentation involving coffee shop owners and consumers. Data analysis followed Miles and Huberman’s interactive model consisting of data reduction, data display, and conclusion drawing. The findings indicate that coffee consumption has shifted beyond fulfilling practical needs and increasingly functions as a symbolic consumption practice. Social media plays a significant role not only as a source of information but also as a medium that constructs representations and meanings associated with coffee shops. Through promotional content, labels, and visual narratives, social media shapes perceptions regarding lifestyle, productivity, and social identity. These meanings are reinforced through coffee shop concepts such as Working from Cafés (WFC), menu innovation, pricing strategies, and spatial arrangements that create symbolic values beyond the practical function of coffee consumption. As a result, coffee shops are no longer consumed merely as places for purchasing beverages but also as social spaces where individuals consume experiences, identities, and symbolic meanings. This study argues that coffee consumption in Pontianak reflects characteristics of consumer society, where consumption increasingly revolves around signs and symbolic values.